2014
DOI: 10.4254/wjh.v6.i6.435
|View full text |Cite
|
Sign up to set email alerts
|

Pooled genetic analysis in ultrasound measured non-alcoholic fatty liver disease in Indian subjects: A pilot study

Abstract: Pooled genetic analysis revealed an association of SNPs in PNPLA3, PARVB, SAMM50 and PZP genes with NAFLD. SNPs in NCAN and PNPLA3 gene were associated with higher levels of ALT, whereas variant SNPs in APOC3, PNPLA3, EFCAB4B and COL13A1 were associated with high triglyceride levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 24 publications
2
21
0
2
Order By: Relevance
“…Recently, a study of monozygotic twins with NASH-related cirrhosis found rs1227756 to be a contributing factor in disease progression (Grove et al, 2016). Additionally, we observed an association between rs1227756 COL13A and higher triglyceride levels, which supports the findings of a study conducted with NAFLD patients in India (Ravi Kanth et al, 2014). Our results differ from those of a recent study that did not observe an association between the rs1227756 variant and the presence of NAFLD in Chinese children (Shang et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Recently, a study of monozygotic twins with NASH-related cirrhosis found rs1227756 to be a contributing factor in disease progression (Grove et al, 2016). Additionally, we observed an association between rs1227756 COL13A and higher triglyceride levels, which supports the findings of a study conducted with NAFLD patients in India (Ravi Kanth et al, 2014). Our results differ from those of a recent study that did not observe an association between the rs1227756 variant and the presence of NAFLD in Chinese children (Shang et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Studies of genetic regions like PNPLA3 , SAMM50 and PARVB support this idea, since variants in these genes have been associated with NAFLD and elevated ALT and AST levels (Flores et al, 2016; Kitamoto et al, 2013; Ravi Kanth et al, 2014). Krawczyk et al found that the combined effect of several SNPs was linked to the presence of elevated ALT levels, as well as NAFLD severity (Krawczyk et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Further, polymorphisms of adiponectin gene have been shown to be associated with severity of liver disease in Asian Indians with NAFLD 50 . In a genomewide association study from South India, Kanth et al 51 recruited 306 subjects and reported that sorting and assembly machinery of the mitochondria 50 (SAMM50), parvin beta (PARVB) and pregnancy zone protein (PZP) genes, in addition to PNPLA3 gene were significantly associated with NAFLD.…”
Section: Other Determinants/correlates Of Nafld In Asian Indiansmentioning
confidence: 99%